2013
DOI: 10.4103/2278-330x.119886
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of salivary gland tumors in Manipur, India: A 10 year study

Abstract: Background:Salivary gland lesions, especially the neoplastic lesions constitute a highly heterogeneous histopathologic group. Several studies have reported a significant difference in the global distribution of salivary gland tumors, but no formal study has been carried out in this part of the globe.Objectives:To document the pattern of various salivary gland tumors in Manipur, a state in North Eastern India.Materials and Methods:This is a 10 years (2002-2011) retrospective study of all salivary gland specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
39
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 16 publications
(16 reference statements)
13
39
2
Order By: Relevance
“…10,14,15 Warthin tumor (13.51%) was the second commonest benign tumor similar to the observation of Chung et al 16 Out of 25 cases of pleomorphic adenomas 18 involved parotid, 4 involved submandibular gland and 3 cases involved minor salivary glands. All the five cases of Warthin tumor affected only the parotid gland, which is similar to the finding reported by Laishram et al 4 In the present series adenoid cystic carcinoma was the most common salivary gland tumor comprising 44.44% cases (4 cases out of 9 malignancies)[ Fig.2]. Ahmad et al and Rewsuwan et al also reported similar observation in their studies.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…10,14,15 Warthin tumor (13.51%) was the second commonest benign tumor similar to the observation of Chung et al 16 Out of 25 cases of pleomorphic adenomas 18 involved parotid, 4 involved submandibular gland and 3 cases involved minor salivary glands. All the five cases of Warthin tumor affected only the parotid gland, which is similar to the finding reported by Laishram et al 4 In the present series adenoid cystic carcinoma was the most common salivary gland tumor comprising 44.44% cases (4 cases out of 9 malignancies)[ Fig.2]. Ahmad et al and Rewsuwan et al also reported similar observation in their studies.…”
Section: Discussionsupporting
confidence: 81%
“…5 Studies by Laishram et al in Manipur and Ahmad et al in Kashmir were also comparable to our study. 4,6 Our study showed high incidence of both benign and malignant tumors in 5 th decade and after 60 years. However Satko et al and Ahmad et al reported the highest incidence of benign tumors in the 3 rd to 4 th decade and malignant tumors in 4 th to 5 th decade of life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations